The Involvement of Women in the Production of Emping Melinjo (Melinjo Chips) to Improve the Economy of Rural Farmer Household - Arsal, Thriwaty (KOMUNITAS: International Journal of Indonesian Society and Culture, 2015)
Womenâ€™s involvement in the production of melinjo chips were related to the low educational level and less skill. They only had skill in producing melinjo chips that they inherited from their parents. Women who worked to produce melinjo chips were only to help their husband to improve their household economy. In addition, collector companies only recognized man as workers; therefore, only man who got the salary. Qualitative research was used as the research method with 10 informants consisted of men and women. Research result indicated that the involvement of women in the production of melinjo chips was marginalized where salary was not calculated despite their involvement in the whole production process. Moreover, there was no recognition for womenâ€™s work and they had no health insurance and social protection from the collector companies.Â